2017
DOI: 10.3389/fcimb.2017.00140
|View full text |Cite
|
Sign up to set email alerts
|

Inactive Gingipains from P. gingivalis Selectively Skews T Cells toward a Th17 Phenotype in an IL-6 Dependent Manner

Abstract: Gingipain cysteine proteases are considered key virulence factors of Porphyromonas gingivalis. They significantly influence antibacterial and homeostatic functions of macrophages, neutrophils, the complement system, and cytokine networks. Recent data indicate the role of P. gingivalis in T cell differentiation; however, the involvement of gingipains in this process remains elusive. Therefore, the aim of this study was to investigate the contribution of danger signals triggered by the gingipains on the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…More recently, it has been demonstrated that P. gingivalis favors T helper cell polarization to a TH17 profile with generation of TH17-related cytokines [30] and that the P. gingivalis induced T cell differentiation shift is highly specific towards a TH17 cell phenotype in an IL-6 dependent manner [31]. Moreover, a periodontitis rat model study showed a variable sitespecific TH17/Treg cell ratio in the oral tissues but detected a TH17 cell increase with a relative Treg cell decrease in peripheral blood, which was proposed to potentially impact development of systemic inflammatory diseases [32].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been demonstrated that P. gingivalis favors T helper cell polarization to a TH17 profile with generation of TH17-related cytokines [30] and that the P. gingivalis induced T cell differentiation shift is highly specific towards a TH17 cell phenotype in an IL-6 dependent manner [31]. Moreover, a periodontitis rat model study showed a variable sitespecific TH17/Treg cell ratio in the oral tissues but detected a TH17 cell increase with a relative Treg cell decrease in peripheral blood, which was proposed to potentially impact development of systemic inflammatory diseases [32].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of IL-6 signaling in dendritic cells led to a significant depletion of the Th17 population without similar effects on other T-cell subsets. These studies unveiled the possibility that Th17 cells are involved in the pathogenesis of periodontitis and confirmed that IL-6 signaling is an attractive target for treatment of this disease ( 49 ).…”
Section: Porphryomonas Gingivalismentioning
confidence: 67%
“…Additional studies have shown that antigen‐presenting cells (eg,. macrophages, dendritic cells) challenged with P gingivalis or Prevotella spp demonstrated increases in IL‐23 within the broader repertoire of inflammatory mediator responses, and P endodontalis LPS elicited IL‐23 linked to enhanced osteoclastogenesis, the cytokine cascade of granuloma tissues and in responses of periodontal ligament cells to LPS . However, IL‐23 in responses of oral epithelial cells is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL‐23 in responses of oral epithelial cells is sparse. A single report describes IL‐23 elevations in immortalized gingival keratinocytes following infection with P gingivalis . The interesting findings with this important regulatory cytokine were its elevated expression with each of the planktonic species that was decreased substantially with the combined biofilms.…”
Section: Discussionmentioning
confidence: 99%